Tetrandrine Ameliorates Rheumatoid Arthritis in Mice by Alleviating Neutrophil Activities. (16th February 2022) - Lu, Qingyi; Jiang, Haixu; Zhu, Qingqing; Xu, Jie; Cai, Yanan; Huo, Guiyang; Yuan, Kai; Huang, Guangrui; Xu, Anlong
Abstract : Rheumatoid arthritis (RA) is a common autoimmune disease worldwide. Neutrophils play critical roles in the onset and development of RA and are the promising target for RA treatment. Tetrandrine is a bis-benzyl isoquinoline alkaloid derived from the traditional Chinese herbal Stephania tetrandra S. Moore. Tetrandrine is effective in alleviating RA by inhibiting macrophage inflammatory response, fibroblast overproliferation, and pannus formation. However, whether tetrandrine regulates the activities of neutrophils in RA is largely unknown. In this study, we adopted adjuvant-induced arthritis (AA) murine model to explore the effect of tetrandrine on RA and neutrophils. Twenty-eight mice were divided into four groups. The control group was injected with PBS in the limbs and treated with PBS by intraperitoneal injection (i.p.) from Day 10 to Day 37. The arthritis murine model was induced by injecting FCA into the ankle joints of hind limbs. The AA group, the AA + TET group, and the AA + DEX group mice were treated with PBS, tetrandrine (6 mg/kg), or dexamethasone (1 mg/kg) i.p. daily, respectively. Arthritic scores were evaluated, and the joint diameter was measured every three days. A cytometric bead assay was performed to measure the concentrations of IFN- γ, TNF- α, and IL-6 in the serum. H&E staining and Safranin O-fast staining were adopted to monitor the tissue changes in the joint. Immunohistochemistry assays were applied to detect the MPO, NE, CitH3, and PAD4 expression levels. To assess the effect of tetrandrine on neutrophil activities in vitro, CCK8 tests were applied to determine cell viability. The qPCR and ELISA were performed to determine IL-1 β and IL-6 expression levels. Immunofluorescence assays were performed to measure the formation of NETs. The results indicated that tetrandrine significantly alleviated the symptoms of RA in terms of the ankle diameter (from 4.629 ± 2.729 to 3.957 ± 0.257; P < 0.01 ) and ankle score (from 4.000 ± 0.000 to 3.286 ± 0.756; P < 0.05 ). Tetrandrine treatment significantly increased the cartilage areas and decreased serum IL-6 significantly (from 5.954 ± 2.127 to 2.882 ± 2.013; P < 0.01 ). The immunohistochemistry assays also showed decreased expression levels of NE, MPO, PAD4, and CitH3 induced by tetrandrine in comparison with the AA group (P < 0.01 ). The qPCR assays and ELISAs showed that tetrandrine had an anti-inflammatory effect in vitro by significantly inhibiting IL-6 (P < 0.01 ). The immunofluorescence assays showed that NET formation induced by PMA could be reduced by tetrandrine (P < 0.01 ). In conclusion, tetrandrine has good efficacy in treating RA by regulating neutrophil-involved inflammation and NET formation.